Spregledan podjetniški potencial mladih: GEM Slovenija 2013 - Rebernik, Miroslav; Tominc, Polona; Crnogaj, Katja; Širec, Karin; Bradač Hojnik, Barbara; Rus, Matej (2014)
Overlooked Entrepreneurial Potential of Youth : GEM Slovenia 2013. The Global Entrepreneurship Monitor (GEM) for the 2013 shows the significantly lower proportion of young established business owners in the 25-34 age group than the overall average. In Slovenia, it amounted to only 7% while in other countries participating in the research this percentage was between 11% and 17%. This rather worrying state is related to low rate of early-stage entrepreneurial activity of young people and the issues related to their employability, which further stems from a high rate of Slovenian young people who are unemployed. It thus seems that young individuals in Slovenia do not perceive business opportunities and are also less successful in transforming these opportunities into more permanent forms of established business ownership activities. Governmental policies should therefore urgently be focused on this age group as this is the group in which the perception of entrepreneurship as a desirable career choice could increase the most if supported by various programmes and activities.
Keywords: Entrepreneurship; Global Entrepreneurship Monitor; Youth Entrepreneurial Activity; Entrepreneurship Career; Governmental Policies; podjetništvo; Globalni podjetniški monitor; podjetniška aktivnost mladih; podjetniška kariera; vladne politike